2015
DOI: 10.3109/10717544.2015.1048488
|View full text |Cite
|
Sign up to set email alerts
|

Albumin corona on nanoparticles – a strategic approach in drug delivery

Abstract: Nanomaterials have been used widely for delivery of therapeutic agents. Protein-nanoparticle (NP) complexes have gained importance as vehicles for targeted drug delivery due to increased ease of administration, stability and half-life of drug, and reduced toxic side effects. Designing of phospholipid-bovine serum albumin (BSA) complexes and stealth NPs with BSA has paved the way for drug delivery carriers with prolonged blood circulation times. Preformed albumin corona has shown to decrease non-specific associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(114 citation statements)
references
References 68 publications
0
112
0
2
Order By: Relevance
“…A complex is formed which is usually isolated by centrifugation. In that reaction albumin is the reducing agent and a stabilizer [43]. The study of the impact of nanoparticles on protein aggregation is an area of considerable research considering their use as anti-inflammatory or anti-neurodegeneratives agents.…”
Section: Discussionmentioning
confidence: 99%
“…A complex is formed which is usually isolated by centrifugation. In that reaction albumin is the reducing agent and a stabilizer [43]. The study of the impact of nanoparticles on protein aggregation is an area of considerable research considering their use as anti-inflammatory or anti-neurodegeneratives agents.…”
Section: Discussionmentioning
confidence: 99%
“…Polymeric NPs can be coated with albumin by various methods [19]. The most common approach is to incubate NPs with albumin and let the protein physically adsorb to the NP surface (physisorption) [10, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that PEG‐based coatings may introduce other problems such as nondegradation and hypersensitivity . Possible alternatives to PEG include synthetic polymers such as polyoxazolin, polyvinyl pyrrolidone, polyacrylamide, zwitterions, and their block copolymers, natural polysaccharides such as dextran, chitosan, hyaluronic acid, and heparin, biomolecules such as polyaminoacids, albumin, and biomembrane, as well as siliconate treatment . Biodegradable polymers including chitosan, poly(phosphoester) and polyglutamic acid have achieved great attention for medical applications since they could be enzymatically hydrolyzed and degraded into nontoxic small molecules and do not accumulate in the body .…”
Section: Safe‐by‐design Strategies For Nanomedicinementioning
confidence: 99%